An fMRI study of theory of mind in individuals with first episode psychosis. (30th November 2018) - Bartholomeusz, Cali F.; Ganella, Eleni P.; Whittle, Sarah; Allott, Kelly; Thompson, Andrew; Abu-Akel, Ahmad; Walter, Henrik; McGorry, Patrick; Killackey, Eóin; Pantelis, Christos; Wood, Stephen J.
Highlights: The social brain is dysfunctional in young people with first episode psychosis. Temporoparietal hypoactivation in FEP was negatively correlated with symptomatology. Aberrant activation was not associated with global social and occupational functioning. Young people with FEP may benefit from interventions that target theory of mind. Abstract: Theory of mind (ToM), the ability to infer one's own and others' mental states, is the social cognitive process shown to have the greatest impact on functional outcome in schizophrenia. It is not yet known if neural abnormalities underlying ToM present early, during the first episode of psychosis (FEP). Fourteen FEP participants and twenty-two healthy control participants, aged 15–25, were included in analyses. All participants had a 3T magnetic resonance imaging scan and completed a block-design picture-story attribution-of-intentions ToM fMRI task, and completed a battery of behavioral social cognitive measures including a ToM task. General linear model analyses were carried out. Post-hoc regression analyses were conducted to explore whether aberrant ToM-related activation in FEP participants was associated with symptomatology and global social and occupational functioning. FEP participants, when compared to healthy controls, had significantly less activity in the right temporoparietal junction, right orbitofrontal cortex and left middle prefrontal/inferior frontal cortex, when making social attributions. Aberrant ToM-related activation in the right temporoparietal junction was associated with severity of overall psychopathology, but not functional outcome. Specific regions of the social brain network, associated with ToM, are dysfunctional in young people with FEP. Future research should determine whether alteration of normal brain functioning in relation to ToM occurs before or during illness onset.